Unrip, a factor implicated in cap-independent translation, associates with the cytosolic SMN complex and influences its intracellular localization - Grimmler, Matthias; Otter, Simon; Peter, Christoph; Müller, Felicitas; Chari, Ashwin; Fischer, Utz (Human molecular genetics, 2005)
Spliceosomal Uridine-rich small ribonucleo protein (U snRNP) assembly is an active process mediated by the macromolecular survival motor neuron (SMN) complex. This complex contains the SMN protein and six additional proteins, named Gemin2-7, according to their localization to nuclear structures termed gems. Here, we provide biochemical evidence for the existence of another, yet atypical, SMN complex component, termed unr-interacting protein (unrip). This abundant factor has been previously shown to form a complex with unr, a protein implicated in cap-independent translation of cellular and viral mRNA. We show that unrip is integrated into a complex with unr or with the SMN complex in vivo in a mutually exclusive manner. In the latter case, unrip is recruited to the active SMN complex via a stable interaction with Gemin7. However, unlike SMN and Gemins, unrip localizes predominantly to the cytoplasm and is absent from gems/Cajal bodies. Interestingly, RNAi-induced reduction of unrip protein levels leads to enhanced accumulation of SMN in the nucleus as evident by the increased formation of nuclear gems/Cajal bodies. Our data identify unrip as the first component of the U snRNP assembly machinery that associates with the SMN complex in a compartment-specific way. We speculate that unrip plays a crucial role in the intracellular distribution of the SMN complex.